KINERJA DIGESTER AEROBIK DAN PENGERING LUMPUR DALAM MENGOLAH LUMPUR TINJA - Ipung Fitri Purwanti (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2003)
The research used aerobic digester reactor in batch system and sludge dryer used sand as media. Variable used were aeration time, oxygen supply system and time of drying. The observed parameter were optimum aerator time, reaction rate coefficient, drying time, and solid content, water content, C/N ratio, and coliform bacteria. The optimum aeration time is 12 days. During the aeration time, microorganism grow at specific growth rate (m) 0,1952/day and the decay rate (kd) 0,5341/day. The air supplay with constant system at 5,5 L/min is better than fluctuation system, because gives C/N content 21:1, that suitable for mature compost standard. The time of drying of digested sludge 14 days at 70% moisture is better than 7 days, with C/N content more than 30:7 and water content close 30 %.